PENETAPAN KADAR ALKALI BEBAS PADA SABUN CUCI KRIM YANG DIJUAL DI MINI MARKET SECARA ASIDIMETRI - Puput Kusuma Dipaningrum; Ade Maria Ulfa; Sudewi Mukaromah Khoirunnisa (Program Studi Analisis Farmasi dan Makanan Universitas Malahayati, 2022)
Laundry soap cream is one PKRT (Household Health) which is used to clean equipment and to wash clothes. The main constituent component of fat and soap is alkaline, where if there is excess base does not react with the excess fat there will be alkali-free. If in the soap containing alkali-free high, it can cause skin irritations such as rough skin, flushed, sometimes there are small spots of water and cause itching. Limit allowed in the free alkali soap cream by the Indonesian National Standard 06-2048-1990 ie a maximum of 0.1%. This study aims to determine the levels of free alkaline detergent contained in the cream is sold in the mini market of Bandar Lampung. The method used is acidimetry, where the principle is the determination of free alkaline by neutralizing acids and bases. In this study HCl titrant used is a strong base that is titrated by using a strong acid, an indicator used is phenolpthalien with stretch pH 8.2 to 9.6 and endpoint occurring from pink to white. From the results obtained with the sample five different brands the average level of alkali-free for sample A: 3.06% B: 2.86%, C: 1.08%, D: 0.40%, E: 1.11 %. Based on the research results obtained showed that the alkali-free in all samples of soap cream does not meet the requirements of the maximum levels of Indonesian National Standard 06-2048-1990 ie 0.1%.